A fluid dynamic investigation of the Big Blade and Macon oar blade designs in rowing propulsion - Caplan, N.; Gardner, T. N. (Journal of Sports Sciences, 2007)
The purpose of this investigation was to examine the fluid dynamic characteristics of the two most commonly used oar blades: the Big Blade and the Macon. Scaled models of each blade, as well as a flat Big Blade, were tested in a water flume using a quasi-static method similar to that used in swimming and kayaking research. Measurement of the normal and tangential blade forces enabled lift and drag forces generated by the oar blades to be calculated over the full range of sweep angles observed during a rowing stroke. Lift and drag force coefficients were then calculated and compared between blades. The results showed that the Big Blade and Macon oar blades exhibited very similar characteristics. Hydraulic blade efficiency was not therefore found to be the reason for claims that the Big Blade could elicit a 2% improvement in performance over the Macon. The Big Blade was also shown to have similar characteristics to the flat plate when the angle of attack was below 90°, despite significant increases in the lift coefficient when the angle of attack increased above 90°. This result suggests that the Big Blade design may not be completely optimized over the whole stroke.